Adjustments to pharmacologic therapies for hemophagocytic lymphohistiocytosis while on extracorporeal support. Issue 6 (10th March 2021) - Weyand, Angela C.; Barbaro, Ryan P.; Walkovich, Kelly J.; Frame, David G.
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is an immune dysregulatory syndrome characterized by severe inflammation and end‐organ damage. Due to significant organ dysfunction, patients often require extracorporeal membrane oxygenation (ECMO) and continuous renal replacement therapy (CRRT). In this report, we describe consideration for adjusting treatment in the context of extracorporeal organ support. We describe agents commonly used and dosing adjustments made in light of extracorporeal organ support. We report six cases that illustrate the feasibility of initiating standard HLH therapies in patients requiring these modalities.